The Borderline Bias in Explicit Emotion Interpretation - Hyniewska, Sylwia; Dąbrowska, Joanna; Makowska, Iwona; Jankowiak-Siuda, Kamila; Rymarczyk, Krystyna (Frontiers in Psychology, 2021)
Atypical emotion interpretation has been widely reported in individuals with Borderline Personality Disorder (iBPD), however empirical studies reported so far mixed results. We suggest that discrepancies in observations of emotion interpretation by iBPD can be explained by biases relating to their fear of rejection and abandonment, i.e.the three moral emotions of anger, disgust and contempt. In our study we hypothesised that iBPD would show a higher tendency to correctly interpret these three displays of social rejection and attribute more negative valence. 28 inpatient iBPD and 28 healthy controls were asked to judge static and dynamic facial expressions in terms of emotions, valence and self-reported arousal evoked by the observed faces. Our results partially confirmed our expectations. iBPD correctly interpreted the three unambiguous moral emotions. Contempt which is a complex emotion with difficult to recognise facial expressions was recognised better by individuals with BPD than by healthy controls. All negative emotions were judged more negatively by iBPD than by controls, but no difference was observed in the neutral or positive emotions. Alexithymia and anxiety trait and state levels were controlled for in all analyses.